CFD analysis and comparison of conventional type and perforated plate type shell tube heat exchangers - İNAN, AHMET TALAT (My University, 2022)
AbstractThe baffle plate is the most important elements affecting not only the thermal efficiency but also the hydraulic performance of shell-tube heat exchangers that can be designed in different types today and can be put into the production phase. Different designs of baffle plates are closely related to thermal performance with pressure drop as well. In this investigation, the design geometry of the shell-tube type was carried out by means of the ANSYS Fluent program.In the analyses, it is purposed to examine the consequences on the heat transfer rate per drop of pressure and not only the pressure’s drop but also the coefficient parameter of heat transfer of the exchangers in which traditional one-piece type baffle plate and perforated type baffle plate are used where the shell side. Here, water is used as the working fluid; it was examined as 1.2, 1.5, 1.8 and 2.1kg/h at four varied mass flow rates (m). As a result, the values compared to the traditional one-piece baffle plate and the perforated type baffle plate. It has been monitored that the heat transfer rates per drop of pressure vary
Keywords: Makina Mühendisliği; Enerji; Diğer; Mühendislik ve Teknoloji; Mechanical Engineering; Energy; Other; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, MEKANİK; ENERJİ VE YAKITLAR; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, MECHANICAL; ENERGY & FUELS; Makine Mühendisliği; Hesaplamalı Mekanik; Otomotiv Mühendisliği; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Enerji (çeşitli); Genel Enerji; Fizik Bilimleri; Computational Mechanics; Automotive Engineering; Renewable Energy, Sustainability and the Environment; Fuel Technology; Energy Engineering and Power Technology; Energy (miscellaneous); General Energy; Physical Sciences